Early measurement of autism risk constructs in the general population: A new factor structure of the First Years Inventory (FYIv3.1) for ages 6–16 months. Issue 5 (3rd March 2022) - Baranek, Grace T.; Sideris, John; Chen, Yun‐Ju; Crais, Elizabeth R.; Turner‐Brown, Lauren; Watson, Linda R.
Abstract: Early detection of autism risk in the community is critical to increasing families' access to early intervention, yet few measures have been developed and tested for the general population of infants <16 months to tap a broader range of autism risk constructs. This study aimed to (a) examine the factor structure of the First Years Inventory, version 3.1 (FYIv3.1), with a sample of 6454 infants 6–16 months, and (b) determine the ability of the resulting factors to discriminate clinical outcome groups at 3 years of age. The FYIv3.1 is a parent‐report tool designed to detect early behavioral risk signs that may be associated with a later diagnosis of ASD and related neurodevelopmental conditions. Factor analytic models were used to determine the number of constructs and inter‐factor correlations. Findings supported a seven‐factor structure: communication, imitation and play (CIP); social attention and affective engagement (SAE); sensory hyperresponsiveness (HYPER); sensory hyporesponsiveness (HYPO); self‐regulation in daily routines (SREG); sensory interests, repetitions, and seeking behaviors (SIRS); motor coordination and milestones (MCM). Mean comparisons on these factors demonstrated significant discrimination of the three outcome groups at age 3 years including those classified as having an ASD diagnosis and/or high autism symptoms, those classified as having other developmental disorders/conditions/concerns, and those classified with no known conditions/concerns. These findings support the validity and multidimensionality of early ASD risk constructs, as well as the potential use of the FYIv3.1 for phenotypic subtyping in the general population, and early detection in a broader age range of 6–16 months in future clinical studies. Lay Summary: The FYIv3.1 is a 69‐item parent‐report questionnaire about infant behaviors that may indicate an elevated likelihood for later neurodevelopmental conditions such as autism. Analyses of responses from 6454 parents of infants 6–16 months indicated that items could be grouped reliably into seven categories. Compared to children with or without other developmental conditions, children in the outcome group with autism spectrum disorder and/or high autism symptoms at age three showed more behavioral risk signs in social‐communication, sensory, and motor domains during infancy.